Rheological and Thermal Analysis of Polystyrene –Kaolin Nanocomposite Prepared by Solution Intercalation Technique. (2016) - Naveen, A.N.; Manoj, N.
Abstract: Polymer-clay nanocomposite of commercial polystyrene (PS) and kaolin were prepared via solution intercalation technique. Organically modified kaolin was used to render kaolin miscible with hydrophobic PS. Vinyl modified kaolin was used for the study. The kaolin was well dispersed in PS solution. Different amounts of nanoclay was added to polystyrene, to analyse the effect of nanoclay concentration in nanocomposite prepared. SEM analysis provides information of the morphology of the polystyrene-clay nanocomposite. Intercalation occurs at low modified clay content, whereas aggregation and agglomeration occurs at high filler content. The thermal analysis and rheological analysis was carried on the PS-Kaolin nanocomposite. The results indicates the difference in property of polystyrene-nanoclay composite with filler loading.